1967
DOI: 10.1084/jem.125.1.91
|View full text |Cite
|
Sign up to set email alerts
|

The Ultrastructure and Function of the Cells in Lymph Following Antigenic Stimulation

Abstract: When a lymph node receives an antigenic stimulus the cell population in the efferent lymph changes and large basophilic cells appear. During a secondary immune response cells of this type may account for over 50% of the cells present in lymph. When examined by electron microscopy, many of these cells were found to be primitive undifferentiated blast cells with many free ribosomes in their cytoplasm and only an occasional piece of endoplasmic reticulum. Their nuclear chromatin was sparse and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
0
2

Year Published

1967
1967
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(47 citation statements)
references
References 24 publications
6
39
0
2
Order By: Relevance
“…It is also of some interest to speculate on the role of the circulating AS cell pool. Some investigators have suggested a surveillance mechanism for these cells (21,22). It is not clear, however, if this surveillance is one for the "primary response" to a foreign antigen or if it is designed for the more rapid response on "secondary" stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…It is also of some interest to speculate on the role of the circulating AS cell pool. Some investigators have suggested a surveillance mechanism for these cells (21,22). It is not clear, however, if this surveillance is one for the "primary response" to a foreign antigen or if it is designed for the more rapid response on "secondary" stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic immunity involves Abs and B and T cells that combine for effective protection against a range of pathogenic agents. Early examinations of lymphocyte migration established that systemic immunity was dependent on circulating lymphocytes, in combination with their passage through the regional lymph nodes (1)(2)(3). The latter structures play a pivotal role in adaptive immunity because of their involvement in lymphocyte priming, particularly postinfection at remote sites, such as the skin or mucosal surfaces.…”
Section: Tissue-resident Memory T Cells and Fixed Immune Surveillancementioning
confidence: 99%
“…(Hall and Morris, 1963;Hall et al, 1967;Denham et al, 1969;Smith and Morris, 1970) and at the peaks of the responses, i.e. between 100 and 200 h after stimulation, 20-40% of the lymph cells were immunoblasts.…”
Section: Methodsmentioning
confidence: 97%